Portfolio-Based Evaluation as a Catalyst for Improving Arabic Writing Instruction and Learning Outcomes - Baity, Anggi Nurul; Aulia Gorda, Mutarto; Aulia Dewi, Rahma (UIN Maulana Malik Ibrahim Malang, 2025)
This study explores the implementation of portfolio-based evaluation in Arabic writing instruction (maharah al-kitābah) at MTs Sunan Kalijaga, Kranding, Mojo, Kediri, as part of efforts to promote learner-centered and reflective pedagogy aligned with the Kurikulum Merdeka. Using a qualitative descriptive method, data were obtained through classroom observation, interviews, and analysis of students’ portfolios consisting of drafts, revisions, and reflections. The findings reveal that portfolio assessment enhances students’ motivation and engagement by allowing them to track their progress and take responsibility for their learning. It also improves writing proficiency, particularly in grammatical accuracy, vocabulary use, and coherence, through iterative feedback and reflection. Moreover, the approach enables differentiated instruction, where tasks are adapted to students’ varying abilities, and strengthens pedagogical relationships between teachers and students through constructive feedback and collaboration. However, several challenges were identified, including time constraints, limited teacher readiness in designing comprehensive rubrics, students’ lack of reflective habits, and inadequate digital infrastructure.